Pilot project, India : the story of rural development at Etawah, Uttar Pradesh - Mayer, Albert (Berkeley : University of California Press, 1958)
This book presents an account of the ideas that Albert Mayer, American architect and planner, and his colleagues advanced in connection with the organization and administration of the pilot community development project in part of the Etawah District of the State of Uttar Pradesh in India.
Includes index.
Includes bibliographical references: p. 345-350.
lje 25/01/2018
Loans
Keywords: Community development; Economic development projects; Etawah (India).